2015
DOI: 10.1074/jbc.m115.642777
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Barley Limit Dextrinase-Limit Dextrinase Inhibitor (LD-LDI) Complex Reveals Insights into Mechanism and Diversity of Cereal Type Inhibitors

Abstract: Background: Barley limit dextrinase (LD), the sole starch debranching enzyme active during seed germination, is regulated by an endogenous inhibitor (LDI). Results: The crystal structure of the LD-LDI complex reveals a new and unexpected binding mode among cereal type inhibitors. Conclusion: A hydrophobic cluster drives the picomolar affinity of LDI. Significance: The molecular understanding of regulation of starch mobilization during germination is augmented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…Moreover, structural information on other debranching enzymes, i.e. Hordeum vulgare limit dextrinase (HvLD;Møller, Vester-Christensen et al, 2015;Møller, Windahl et al, 2015), Bacillus stearothermophilus neopullulanase (Hondoh et al, 2003), Chlamydomonas reinhardtii isoamylase I (Sim et al, 2014) and Pseudomonas amyloderamosa isoamylase (Katsuya et al, 1998) have been deposited in the Protein Data Bank (PDB; http://www.rcsb.org/). Cyclodextrins (CDs) are cyclic oligosaccharides consisting of -1,4-glycosidic linked -d-glucose units and are known to occur as three types: -CD (six glucose units), -CD (seven glucose units) and -CD (eight glucose units) (Szejtli, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, structural information on other debranching enzymes, i.e. Hordeum vulgare limit dextrinase (HvLD;Møller, Vester-Christensen et al, 2015;Møller, Windahl et al, 2015), Bacillus stearothermophilus neopullulanase (Hondoh et al, 2003), Chlamydomonas reinhardtii isoamylase I (Sim et al, 2014) and Pseudomonas amyloderamosa isoamylase (Katsuya et al, 1998) have been deposited in the Protein Data Bank (PDB; http://www.rcsb.org/). Cyclodextrins (CDs) are cyclic oligosaccharides consisting of -1,4-glycosidic linked -d-glucose units and are known to occur as three types: -CD (six glucose units), -CD (seven glucose units) and -CD (eight glucose units) (Szejtli, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray structure of barley LD (PDB ID: 4CVW) (Møller et al, 2015a) was obtained from the RCSB Protein Data Bank. The LD inhibitor was removed from this structure.…”
Section: Systems Preparationmentioning
confidence: 99%
“…Several crystal structures of HvLD have been reported (Vester-Christensen et al, 2010;Møller et al, 2012a, Møller et al, 2015a. The HvLD structure contains four domains (Vester-Christensen et al, 2010) (shown in Figure 1): the N-terminal domain, a carbohydrate binding module 48 (CBM48), a catalytic (β/α) 8 domain containing the two catalytic residues (Asp473, nucleophile; Glu510, general acid/base) and the transition-state stabilizer (Asp642), and a C-terminal domain.…”
Section: Introductionmentioning
confidence: 99%
“…Thus some plants use inhibitors in defence against pests as seen by the structure of a cereal-type inhibitor RBI (Ragi bifunctional a-amylase/trypsin inhibitor) in complex with an insect a-amylase from yellow mealworm (Tenebrio molitor) (PDB: 1TMQ) [63]. The barley LD is regulated by an endogenous limit dextrinase inhibitor (LDI) with picomolar affinity and the LD:LDI structure was solved recently (PDB: 4CVW; Figure 3c) [64]. LDI is also a cereal-type inhibitor, but with a role in controlling LD activity rather than in pest defence [64].…”
Section: Inhibitors Of Starch Modifying Enzymesmentioning
confidence: 99%
“…The barley LD is regulated by an endogenous limit dextrinase inhibitor (LDI) with picomolar affinity and the LD:LDI structure was solved recently (PDB: 4CVW; Figure 3c) [64]. LDI is also a cereal-type inhibitor, but with a role in controlling LD activity rather than in pest defence [64]. Remarkably, although LDI belongs to the cereal-type inihibitor family it uses a fundamentally different orientation in binding ( Figure 3d) and has a unique motif that stabilizes the enzyme complex through an intermolecular hydrophobic cluster ( Figure 3c).…”
Section: Inhibitors Of Starch Modifying Enzymesmentioning
confidence: 99%